Cis-Bis(2,2′-Azopyridinido)dicarbonylruthenium(II) - Tsugiko Takase; Shuya Kainuma; Takatoshi Kanno; Dai Oyama (Molbank, 2021)
An [Ru(apy)2Cl2] precursor (apy = 2,2′-azopyridine) in 2-methoxyethanol was heated under a pressurized CO atmosphere to afford a diradical complex, [Ru(apy·−)2(CO)2], containing one-electron-reduced azo anion radical ligands. The electronic states of the complex were characterized by spectroscopic techniques and computational studies. Magnetic measurements revealed the existence of antiferromagnetic interactions in the diradical complex.